KONDISI LINGKUNGAN DAN PERILAKU MASYARAKAT DENGAN KEBERADAAN JENTIK NYAMUK DI DAERAH ENDEMIS DEMAM BERDARAH DENGUE - Maydinar, Dian Dwiana; Sutrisna, Marlin; Noptriana, Dian (STIKES Syedza Saintika Padang, 2024)
Dengue hemorrhagic fever is a disease that can cause death caused by the Dengue virus, where the Aedes Aegypri mosquito is the main vector and the Aedes Abbopictus mosquito is the potential vector. This study aims to determine the relationship between environmental conditions and community behavior with the presence of mosquito larvae in Dengue Hemorrhagic Fever endemic areas. This research is a type of analytic survey research using a cross sectional research design. The population in this study were all households in RT 12, Rawa Makmur sub-district, Bengkulu city, totaling 80 families. Sampling in this study using a total sampling method totaling 80 families. Data collection techniques using primary data and secondary data. Data analysis used univariate analysis and bivariate analysis with Chi-Square Test. The results of this study showed that out of 80 respondents, 64 (80.0%) respondents had unhealthy environmental conditions, 55 (68.8%) respondents had negative community behavior, 58 (72.5%) respondents found the existence of mosquito larvae outside or inside the house. There is a significant relationship between environmental conditions and the presence of mosquito larvae; There is a significant relationship between people's behavior and the presence of mosquito larvae. It was concluded in the study that the existence of mosquito larvae inside and outside the home was influenced by an unhealthy environment and negative community behavior. It is hoped that the community will have a healthy lifestyle and maintain a healthy environment.Keywords: Mosquito Larvae, Environmental Conditions, Community Behavior.